Attentional avoidant biases as mediators in the association between experiential avoidance and blood pressure in dementia family caregivers. (4th May 2018) - Márquez-González, María; Cabrera, Isabel; Losada, Andrés; Knight, Bob G.
ABSTRACT: Objectives: Experiential avoidance in caregiving (EAC) has been found to be related with dementia family caregivers´ distress and blood pressure (BP). The association between EAC and avoidant attentional biases to emotional stimuli in dementia caregivers, and the potential mediating role of these attentional biases in the association between EAC and increased BP are explored. Method: Seventy nine dementia family caregivers performed a dot-probe task with emotional pictures (distressing and positive) varying in content (general vs. caregiving-related (CR)) and time of exposure (100 vs. 500 ms). They also completed measures of EAC, anxiety, depression, alexithymia and rumination, and their BP was measured. Results: EAC was associated with avoidant attentional biases to CR emotional pictures and negative pictures in general at 100 ms. Experiential Avoidance in Caregiving Questionnaire (EACQ) 'avoidant behaviors' and EACQ 'intolerance of negativity' factors were associated with diastolic and systolic BP, respectively, with attentional avoidance of CR emotional pictures (distressing and positive, respectively) mediating this association. Conclusion: Attentional avoidance of CR emotional stimuli may be the link between EAC and increased BP, as it prevents emotional processing and facilitates the maintenance of physiological activation. EAC may pose a risk for cardiovascular disease in dementia caregivers.